Let My People Live: Faith and Struggle in Central America - Teekoy, Mathew C`` (Journal of Dharma, 1992)
Gordon Spykman, Lance Grahn, Guillermo Cook, Sidney Rooyr Michel Dodson, John Stam, Let My People Live: Faith and Struggle in Central America, Grand Rapids, Michigan: William B. Eerdmans Publishing Company, 1988, pp. 271 .